Justifying Bill 18: A Critique of Kymlicka’s Comprehensive Neutrality - Tanchuk, Nick (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2014)
Manitoba’s Bill 18 provides students the legal right to form gay-straight alliance student groups within denominational and dissentient schools. Religious opponents of Bill 18 claim that the law unjustifiably imposes a homogenous moral worldview on religious families. I argue that if we appeal to Will Kymlicka’s comprehensive neutralist theory of political morality to justify Bill 18, the religious complaint is problematically vindicated. I argue that Kymlicka appeals to two bases of neutrality that ultimately fail to distinguish his view from the perfectionist theories of political morality that he officially rejects. Due to this internal inconsistency, the priority of Kymlicka’s preferred moral practices remains unjustified. For those of us who believe that Bill 18 is morally justified, an alternative approach to explaining this intuition is required.